2017
DOI: 10.1002/ejic.201701184
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Unusual Properties of Tetragonal Pb‐Containing Oxymolybdates Based on La2MoO6

Abstract: Polycrystalline (PbO) x (La 2 MoO 6 ) (1-x)/2 (x = 0, 0.05, 0.1, 0.2, 0.34, 0.4) samples have been prepared by solid-state reactions near 900°C. Phase-pure compounds with the layered tetragonal La 2 MoO 6 structure have been obtained in the range 0 ≤ х ≤ 0.34. Pb doping of La 2 MoO 6 has been shown to cause [a] M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…They were shown to exhibit a piezoelectric response at room temperature and undergo a reversible first‐order ferroelectric phase transition near 600°C, where their conductivity rises sharply. Such behavior was observed previously for Pb‐doped Ln 2 MoO 6 oxymolybdates 26,27 . They have a layered tetragonal structure made up of MoO 4 tetrahedra and LnO 8 cubes, as in the case of Ln 5 Mo 3 O 16 28,29 …”
Section: Introductionsupporting
confidence: 78%
“…They were shown to exhibit a piezoelectric response at room temperature and undergo a reversible first‐order ferroelectric phase transition near 600°C, where their conductivity rises sharply. Such behavior was observed previously for Pb‐doped Ln 2 MoO 6 oxymolybdates 26,27 . They have a layered tetragonal structure made up of MoO 4 tetrahedra and LnO 8 cubes, as in the case of Ln 5 Mo 3 O 16 28,29 …”
Section: Introductionsupporting
confidence: 78%
“…The appearance of the above features in the properties of NaLn 4 Mo 3 O 15 F compounds may be due to very insignificant structural changes since their diffractograms do not differ from that of the pure Nd 5 Mo 3 O 16 . It should be noted that the appearance of ferroelectric‐superionic phase transition was also observed in lead doped oxymolybdates Ln 2 MoO 6 (Ln = La, Nd) with a layered tetragonal structure having a fluorite‐like Ln2O2 layer and close in composition to Ln 5 Mo 3 O 16 molybdates …”
Section: Discussionmentioning
confidence: 85%
“…They were found to be made up of fluorite layers, each containing two sheets of NdO 8 or LaO 8 polyhedra, with a sheet of isolated MoO 4 tetrahedra sandwiched between them. Analysis of X-ray diffraction data for (PbO) x (Nd 2 MoO 6 ) (1-x)/2 and (PbO) x (La 2 MoO 6 ) (1-x)/2 samples, doped with divalent Pb (Voronkova et al, 2016(Voronkova et al, , 2017, indicated that the layered tetragonal phase had an extended stability region. Near 1073 K, an antiferroelectric phase transition was identified, due to the transformation of the I4 1 /acd phase into an I " 4 42m phase on cooling.…”
Section: Introductionmentioning
confidence: 99%
“…However, doping of the oxymolybdates, e.g. with Pb, was found to cause drastic changes in their conductivity and other properties, as mentioned above (Voronkova et al, 2016(Voronkova et al, , 2017. Among other bivalent impurities doping Nd 2 MoO 6 , the structure with magnesium is known (Voronkova et al, 2019).…”
Section: Introductionmentioning
confidence: 99%